Biological Phosphorus and Nitrogen Removal from Wastewater Using Moving Bed Biofilm Reactor (MBBR) - Mudhaffar S. Al-Zuhairy; Zainab Bahaa; Walaa S. Mizeel (Engineering and Technology Journal, 2015)
In this research, an experimental study to evaluate nutrient removal from Al-Rustamiyah wastewater by a moving bed biofilm process was investigated.The moving bed biofilm reactorMBBR consisted of five reactors in series with one anoxic reactor MBBR-1, two aerobic reactor MBBR-2 and MBBR-3, outlet chamber and the flocculation part with dosing unit, that were operated continuously at different loading rates of phosphorus and nitrogen.The MBBR tankswere filled with suspended plastic carriers (AnoxKaldnes K5), with a 50% filling ratio. Under optimum conditions, almost complete nitrification with average ammonium removal efficiency of 82% was achieved.The average phosphorus and total nitrogen removal efficiencies were 76.79% and70%, respectively.